Isolated traumatic avulsion of medial rectus at its proximal origin: A surgical diagnosis - Joshua Rooney; Lakshmi Venkatakrishnan; Mohammed Al-Gholmy; Peter A. Brennan (Elsevier, 2024)
A 16-year-old male presented with blunt force trauma to the left peri-orbital region. He complained of diplopia and restricted adduction of the left eye. Computed tomography (CT) imaging revealed left medial orbital wall fracture involving the medial rectus muscle. Upon operating, the medial rectus was discovered to have been avulsed at its origin. We discuss the diagnosis and management of this rare complication.